A cupful of light - Mokhtar, Makhfudzah; Abiola, Taiwo Ambali; Mohamed, Zamili; Mohd Saidin, Sathzura; Mohamad Tukijan, Siti Noradhlia; Mokhtar, Mumtaz (Universiti Putra Malaysia Press, 2017)
This artefact presents programmable lighting in water-filled cups positioned on a rack, as a means of illustrating some characteristics of light. When the light travels from air to water (in the cup), light refraction occurs. As a result, visual impairment can be observed when objects are seen in the two different media. Objects in the water seem to radically change position as we look at them from different viewpoints of the cup.